Pemisahan zarah mengguna teknik ayak: Kesan parameter pengoperasian ke atas kecekapan - Siti Masrinda Tasirin; Chang , Wun Ching (2000)
Separation of solid mixtures of different particle sizes into two size grades by means of a screening surface is widely used. For thousands of years the fundamental principle of screening has been and still is maintained. Despite of the advantages such as easy operation and low cost of maintenance, the overall efficiency of the process is of importance for optimization purposes. In this case, investigation on the effect of several operating parameters such as time, vibration frequency, percentage of coarse (oversize) in the feed material and total loading on the overall efficiency of the separation process has been carried out using solid mixtures of sand and glass beads. A general form of empirical correlation has been obtained, from which suitable operation conditions for optimum process efficiency may be determined